Optimizing Railway Track Management through Life Cycle Cost Analysis: A Comprehensive Review - Rachmad Indrakusuma; Bagus Budiwantoro; Satrio Wicaksono (Jurnal Teknologi dan Manajemen, 2024)
This paper presents a comprehensive examination of Life Cycle Cost (LCC) analysis as applied to railway track systems, with a focus on optimizing the economic and operational performance of railway infrastructure over its entire lifespan. The study begins with an exploration of existing LCC models and their applications in railway track analysis, highlighting the importance of LCC as a decision-making tool for infrastructure management. It then delves into the integration of degradation models for key track components such as ballast, rails, and sleepers, and how these models contribute to a more accurate and effective LCC analysis.The paper further reviews several case studies to illustrate the practical application of LCC analysis in real-world scenarios. These include an analysis of alternative railway track support materials for the Sydney Harbour Bridge, an evaluation of the slab track monoblock sleeper system for the Indonesian Urban Metro Railway Project under uncertainty, and a life cycle cost, energy, and carbon assessment of the Beijing-Shanghai High-Speed Railway. Each case study provides insights into the methodologies used for LCC analysis and the resulting implications for railway infrastructure management.The findings of this paper underscore the significance of LCC analysis in guiding the maintenance and renewal policies of railway tracks, ensuring cost-effectiveness while maintaining safety and reliability. The paper concludes with recommendations for the adoption of advanced LCC models and maintenance strategies, emphasizing the need for future research to address uncertainties in system performance and to further refine these models for enhanced decision-making in railway track management.